The antecedents of organizational citizenship behavior in Jabatan Hal Ehwal Agama Islam Pulau Pinang (JHEAIPP) / Siti Norshahira Nabilah Romazai - Romazai, Siti Norshahira Nabilah (2016)
The purpose of this paper is to understand various antecedents of organizational citizenship behavior (OCB). Affective commitment, organizational justice and transformational leadership were three independent variables chosen for the study and one moderator that is psychological empowerment. Standard questionnaires were used to collect data and the sample of 235 employees from Jabatan Hal Ehwal Agama Islam Pulau Pinang (JHEAIPP) formed the source of data. The findings indicated that both affective commitment and transformational leadership have a positive relationship with organizational citizenship behavior whereas organizational justice has a negative relationship with organizational citizenship behavior. It also resulted that psychological empowerment does not moderate the relationship between transformational leadership and organizational citizenship behavior.